Association between COMISA and cardiovascular disease: Evidence from the TURKAPNE registry - Yüksel Peker; Aylin Pihtili; Esen Kiyan; Mehmet Sezai Tasbakan; Semih Arbatli; Senay Aydin; Aykut Cilli; Neşe Dursunoglu; Burcu Baran; Özen K Basoglu (PLoS ONE, 2026)
Background Comorbid insomnia and obstructive sleep apnea (COMISA) is increasingly recognized as a distinct clinical entity, yet its relationship with cardiovascular disease (CVD) remains incompletely understood. We aimed to investigate the association between COMISA and CVD in a large clinical sleep cohort. Methods Using data from the TURKAPNE registry, we analyzed 12,715 adults referred for sleep evaluation and classified participants into four mutually exclusive sleep phenotypes: neither OSA nor insomnia (n = 910), insomnia only (n = 388), OSA only (n = 8,142), and COMISA (n = 3,275). The prevalence of CVD was compared across groups. Multivariable logistic regression models were used to examine associations between COMISA and CVD after adjustment for age, sex, body mass index, education level, smoking status, airway disease, diabetes mellitus, and psychiatric comorbidity. Results The prevalence of COMISA was higher among individuals with CVD compared with those without CVD (31.6% vs. 22.7%; p < 0.001). In contrast, the distribution of insomnia alone and OSA alone showed only minor differences by CVD status. In multivariable analysis, CVD was independently associated with COMISA (odds ratio 1.108, 95% confidence interval 1.006–1.220; p = 0.038), although the magnitude of this association was modest. Female sex, diabetes, airway disease, psychiatric disease, lower educational status, and current smoking were also independently associated with COMISA. Conclusion In this large registry-based cohort, COMISA was more prevalent among individuals with CVD, supporting the concept that it represents a clinically distinct phenotype with an increased cardiometabolic burden. However, the modest effect size suggests that COMISA is influenced by a broader interplay of behavioral and metabolic factors.